Determination of Individual Innovative Behaviours, Affecting Factors, and Barriers in Operating Room Workers - Özlem Bilik; Melike Duran; Hale Turhan Damar; Gülcan Öztürk Kaynar (Association of Nurse Managers, 2021)
Aim: This study aims to determine the innovative behaviours of healthcare professionals in the operating room and the factors that affect and barrier factors. Method: This descriptive study was carried out in the operating room of a university hospital in western Turkey between March-September 2020. The study sample consisted of 145 people who agreed to participate in the study, from physicians, nurses, and operating room technicians working in the operating room of the university hospital where the study was carried out. The data collection tools of the study were the 'Nurse Information and The Factors Influencing and Barriers Innovativeness Identification Form' and 'Individual Innovativeness Scale'. The data's statistical analysis used number-percentage distributions, Independent groups t-test, ANOVA, Mann Whitney U test, Kruskal Wallis test, and Spearman correlation analysis. Results: It was determined that the mean score of the individual innovativeness scale of the healthcare professionals participating in the study was 57.52 +- 5.14 and included in the 'traditional' category. When evaluated according to their profession types, nurses and operating room technicians were in the 'traditionalist' category, and physicians were in the 'sceptic' category. A statistically significant difference was found between the individual innovation scores of the healthcare professionals, according to their occupation type, their participation in the scientific meeting on innovation, their status of knowing the concept of innovativeness, and their status of receiving education about innovation. Conclusion: According to our findings, it is recommended that the institution should determine supportive and motivating approaches for operating room employees to receive training in terms of individual innovativeness, to improve their level of innovativeness, and to eliminate the obstacles they face.